Separate neural pathways process different decision costs - Rudebeck, P; Walton, M; Smyth, A; Bannerman, D; Rushworth, M (2006)
Behavioral ecologists and economists emphasize that potential costs, as well as rewards, influence decision making. Although neuroscientists assume that frontal areas are central to decision making, the evidence is contradictory and the critical region remains unclear. Here it is shown that frontal lobe contributions to cost-benefit decision making can be understood by positing the existence of two independent systems that make decisions about delay and effort costs. Anterior cingulate cortex lesions affected how much effort rats decided to invest for rewards. Orbitofrontal cortical lesions affected how long rats decided to wait for rewards. The pattern of disruption suggested the deficit could be related to impaired associative learning. Impairments of the two systems may underlie apathetic and impulsive choice patterns in neurological and psychiatric illnesses. Although the existence of two systems is not predicted by economic accounts of decision making, our results suggest that delay and effort may exert distinct influences on decision making. © 2006 Nature Publishing Group.